Capacitance-to-voltage converter for capacitance measuring system - Arfah, Nurul; Alam, A. H. M. Zahirul; Khan, Sheroz (2011)
The objective of this paper is to provide a lower range capacitance value in a wider range of detection to be used in high frequency system. This is achieved by designing the Op-amp using CMOS 0.13-m technology using switched-capacitor technique. Evaluation of the circuit is based on analytical approach and the simulation is carried out using the PC based Simulation Program for Integrated Circuit Emphasis (PSpice). Differential parameter is optimized to obtain optimum results. The results shows that the switched-capacitor technique used in this capacitance-to-voltage converter circuit experience less supply voltage, wider capacitance detection range, high frequency, low power dissipation loss and provide two detections range in pico and femto Farad range.